Production of coffee robusta (Coffea canephora) with biomass recycling from three forage species during the dry season - Franco Vera, Argenis Ariel (2025)
In Ecuador, Robusta coffee production is key for small farmers thanks to favorable microclimates. At the Sacha-Wiwa experimental center (Cotopaxi), the production of the Napo payamino, Ecorobusta, and Conilón cultivars was evaluated during the dry season, using recycled biomass from mucuna (Mucuna pruriens), kudzu (Pueraria phaseoloides), and golden button (Tithonia diversifolia) forage crops.  A randomized complete block experimental design was applied, and production was measured every 30 days up to 150 days. The Ecorobusta cultivar obtained the highest production (143,88 kg/10 plants), highlighting the use of kudzu as a forage plant, with 128,88 kg/10 plants. In addition, adequate nutrient levels were maintained in the soil. The study concludes that the use of forage crops, especially kudzu, improves coffee yield and soil fertility.